Parental Benefits and Mothers Labor Market Outcomes in the Medium Run - Sebastian Schmitz; Jochen Kluve (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Increasing mothers labor supply is a key policy challenge in many OECD countries. Germany recently introduced a generous parental benefit that allows for strong consumption smooth- ing after childbirth and, by taking into account opportunity costs of childbearing, incentivizes working women to become mothers and return to the labor force rapidly. Using a sharp regression discontinuity design, we estimate policy impacts for the short-run (first two years after childbirth) as well as for the medium-run (i.e. 3-5 years after childbirth) and find significant and striking patterns: First, medium-run effects on mothers employment probability are positive, significant and large, for some subgroups ranging up to 10 per cent. The effects are driven by gains in part-time but not full-time employment. We also find significant increases in working hours. Second, the probability of job continuity rises significantly, i.e. mothers return to their pre-childbirth employer at higher rates. Third, employers reward this return to work by raising job quality significantly and substantially. We argue that these findings are related to an anchor effect: the new parental benefit defines a societally preferred point in time at which mothers return to work after childbirth.
Keywords: I31; J13; J18; 330